FOOD HABITS OF SPOTTED BARB, SILVER BARB, THREE-SPOT GOURAMI, AND MARBLE GOBY IN RAWA PENING LAKE, SEMARANG: KEBIASAAN MAKAN WADER BINTIK DUA, TAWES, SEPAT RAWA, DAN BETUTU DI DANAU RAWA PENING, SEMARANG - Rahman, Arif; Dewi, Shilfi Rohmatika; Jati, Oktavianto Eko (Jurnal Teknologi Perikanan dan Kelautan, 2026)
One of the fishery potentials in Rawa Pening Lake, Semarang Regency, is the indigenous fish. The indigenous fish in this lake have declined due to changes in water quality, intensive fishing activities, and interspecies competition for resources. Some indigenous fish species in this lake include the spotted barb, silver barb, three-spot gourami, and marble goby. The purpose of this study was to analyze the food composition of four indigenous fish species. This study was conducted from October to December 2023. The sampling locations consisted of three stations at different depths (0, 1, and 2 m). Food composition analysis used the index of preponderance. This study found that four indigenous fish of Rawa Pening Lake utilize litter as the main food, phytoplankton as a complementary and additional food source. Zooplankton serve as an additional food source for spotted barb and three-spot gourami. Small fish serve as additional food for the marble goby. These differences in fish diet composition are due to adaptation to available food sources in the water.